Effect of Cryoprotectans and Cryopreservation on Physiological and Some Biochemical Changes of Hopea odorata Roxb. Seed - Laila Ainur Rohmah; Dian Latifah; Fitri Fatma Wardani; Aulia Hasan Widjaya; Kumala Dewi (Journal of Tropical Biodiversity and Biotechnology, 2022)
Hopea odorata Roxb. is a forest plant from Dipterocarpaceae family that has important economic and ecological functions in the ecosystem.  Generative propagation of H. odorata is limited because of its recalcitrant seed that cannot be stored for long periods at room temperature or even at low temperature. Cryopreservation is a seed storage technique that has the potential to prolong the shelf life of recalcitrant seeds. The aim of this study was to evaluate the effect of cryoprotectant and cryopreservation treatment on seed viability and biochemical change (electrolyte leakage, total malondialdehyde, total phenol) of H. odorata seeds. Fresh seeds of H. odorata were treated with two types of cryoprotectans namely PVS1 as non penetrating cryoprotectant and PVS2 as penetrating cryoprotectant, each type of cryoprotectant with four different concentrations (25, 50, 75 or 100%(w/v)) and four different immersion times (30, 60, 90 or 120 mins). Seeds were then stored in two different temperatures, at room temperature (28±2⁰C) or in liquid nitrogen (-196±2⁰C) for 24 hours to evaluate the cryoprotectant toxicity. The results showed that H. odorata seeds stored at room temperature and immersed either in 100%, 75% or 50% of PVS1 possess a higher viability as well as germination percentage, germination rate, vigour index and maximum growth potensial. In addition, they have lower value of electrolyte leakage, total malondialdehyde and total phenol compared to those seeds treated with PVS2. Meanwhile, both type of cryoprotectants and cryopreservation treatment in this study have not been able yet to increase seed viability of H. odorata. Cryopreservation treatments caused an increase in the total of malondialdehyde and electrolyte leakageas and these leads the inability of  H. odorata seeds to germinate. PVS1 cryoprotectant seems to cause less toxic effects on H. odorata seeds but it can not prevent the negative impact of cryopreservation treatment.